2014
DOI: 10.1108/ijse-10-2012-0196
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic determinants of protein and calorie consumption and potential risk of protein-energy malnutrition among households in South-West Nigeria

Abstract: Purpose – The study aimed to investigate the problem of malnutrition among Nigerian households with emphasis on protein and calorie intake. Design/methodology/approach – Multi-stage random sampling approach was used to select 321 household members drawn from a total of 80 households. A combination of descriptive and inferential statistics was applied in analysing the data. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The study of Walpole et al conducted in 2012 (20) estimated an average body mass of 60·7 kg for African adults, both male and female, which was used in the present review as a reference weight when adult body weight was not reported in the study. The level of satisfaction (LOS), which is a measure of protein intake adequacy, as reported in 2014 by Akerele et al (4) , was calculated by dividing the mean protein intake by the calculated recommended daily protein intake for the participants (both EAR and RDA). A LOS above 100 % EAR/RDA means that the protein intake can be considered adequate.…”
Section: Protein Intake Adequacymentioning
confidence: 99%
See 4 more Smart Citations
“…The study of Walpole et al conducted in 2012 (20) estimated an average body mass of 60·7 kg for African adults, both male and female, which was used in the present review as a reference weight when adult body weight was not reported in the study. The level of satisfaction (LOS), which is a measure of protein intake adequacy, as reported in 2014 by Akerele et al (4) , was calculated by dividing the mean protein intake by the calculated recommended daily protein intake for the participants (both EAR and RDA). A LOS above 100 % EAR/RDA means that the protein intake can be considered adequate.…”
Section: Protein Intake Adequacymentioning
confidence: 99%
“…1). Protein-rich foods are usually expensive and not all households have the purchasing power to acquire them (4) . Therefore, it can be speculated that protein deficiency is more prevalent in northern Nigeria since there are fewer financial resources available to buy protein-rich foods.…”
Section: Protein Intake Adequacymentioning
confidence: 99%
See 3 more Smart Citations